STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PERUMAHAN DI GREEN RIVER CITY BEKASI (Studi Kasus di PT. Artha Bangun Pratama). - Rosa Lesmana (Inovasi, 2016)
MARKETING STRATEGIES TO INCREASE SALES HOUSING IN GREEN RIVER CITY   BEKASI (Case Study in PT. Artha Bangun Pratama). This study aims to determine the variables that are strengths, weaknesses, opportunities and threats, as well as to determine the position of the business at IE matrix. This research method is a combination of qualitative research and quantitative based on SWOT analysis, BCG matrix IE and analysis. The population in this study include the top management of seven people by involving several experts and authorities to confirm specifically related to the external environment. The analysis showed that the variables which the strength is location conveniently close to statsiun and the city center, complete facilities, the price adjustment, the intensity of the sale, service quality and competence of employees, inflation and the exchange rate against the US dollar stabilized, development of information technology, and the preservation of natural resources in the surrounding residential neighborhood, while the threat is the growth rate of real estate increased. At present and in the future are in the position of the first cells that grow and develop (grow and develop). Formulation of marketing strategies that can be applied is the market penetration strategy, market development, and product development. Based on the research results it can be suggested  that augment, provide special pricing to consumers, more heavily in the promotion, conducted training, as well as a meeting (gathering) regularly. Keywords: SWOT analysis, BCG analysis, Marketing Strategy, Sales Housing.